Illegitimate Tasks and Employees’ Turnover Intention: A Serial Mediation Model - Zeng, Xiaoye; Huang, Yafu; Zhao, Shouying; Zeng, Lianping (Frontiers in Psychology, 2021)
In the historical and cultural context of developing countries such as China, illegitimate tasks have become an important source of workplace pressure for employees. Guided by the framework of the stress-as-offense-to-self theory, effort–reward imbalance model, and dual-process work-home interference model, we explored how illegitimate tasks enhance turnover intention. A total of 474 employees from China effectively completed the online survey. The results showed a statistically positive correlation between illegitimate tasks, effort–reward imbalance, work–family conflict, and turnover intention. Illegitimate tasks can affect intention to quit directly and through two indirect paths: the separate intermediary effect of work–family conflict and the continuous mediating role of effort–reward imbalance and work–family conflict. The results indicated that illegitimate tasks enhance employees’ intention to quit through the role of effort–reward imbalance and work–family conflict. This study contributes to understanding the mechanisms underlying the relation between illegitimate tasks and workers’ turnover intention in the context of Chinese history and culture. Additionally, the findings have implications for reducing employees’ propensity to quit.